2021
DOI: 10.3390/ijms23010225
|View full text |Cite
|
Sign up to set email alerts
|

Linoleic Acid Upregulates Microrna-494 to Induce Quiescence in Colorectal Cancer

Abstract: Cancer dormancy is a state characterized by the quiescence of disseminated cancer cells, and tumor recurrence occurs when such cells re-proliferate after a long incubation period. These cancer cells tend to be treatment resistant and one of the barriers to successful therapeutic intervention. We have previously reported that long-term treatment of cancer cells with linoleic acid (LA) induces a dormancy-like phenotype. However, the mechanism underpinning this effect has not yet been clarified. Here, we investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 36 publications
(50 reference statements)
1
10
0
Order By: Relevance
“…Suppression of miR-494 by the lncRNA PCAT29 promotes PTEN expression [27], while a similar action by the lncRNA SBF2-AS1 promotes FGFR2 expression [28]. The downregulation of NQO1 by miR-494 has been shown to inhibit the Nrf2 signaling pathway [20], and we previously reported that miR-494 induces a quiescent state in cancer cells by suppressing oxidative phosphorylation [29].…”
Section: Discussionmentioning
confidence: 97%
“…Suppression of miR-494 by the lncRNA PCAT29 promotes PTEN expression [27], while a similar action by the lncRNA SBF2-AS1 promotes FGFR2 expression [28]. The downregulation of NQO1 by miR-494 has been shown to inhibit the Nrf2 signaling pathway [20], and we previously reported that miR-494 induces a quiescent state in cancer cells by suppressing oxidative phosphorylation [29].…”
Section: Discussionmentioning
confidence: 97%
“…For example, Ogata et al noticed that linoleic acid can lead to upregulation of miR-494, further inducing cancer dormancy. 26 Linoleic acid, an essential omega-6 polyunsaturated fatty acid, has important roles in cell function and metabolism. Recent studies suggest it may be involved in the pathogenesis of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous epidemiological and animal experimental studies have shown that polyunsaturated fatty acids (PUFAs) have a growth-inhibitory effect on mammary ( 38 ) and colorectal cancer ( 39 ). One of the important PUFAs commonly present in diets is linoleic acid.…”
Section: Discussionmentioning
confidence: 99%